2017
DOI: 10.17219/acem/65430
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vitamin D deficiency on eradication rates of Helicobacter pylori

Abstract: Background. Helicobacter pylori eradication therapy improves the healing of various gastro-duodenal diseases such as chronic gastritis and peptic ulcer, and also reduces gastric cancer incidence. Several studies have reported on risk factors other than antibiotic resistance related to Helicobacter pylori eradication failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 27 publications
2
42
0
1
Order By: Relevance
“…Several clinical studies have illustrated that vitamin D analogs may have anti‐ H. pylori antimicrobial effects . Some studies have also found that serum vitamin D levels may have an impact on H. pylori eradication …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several clinical studies have illustrated that vitamin D analogs may have anti‐ H. pylori antimicrobial effects . Some studies have also found that serum vitamin D levels may have an impact on H. pylori eradication …”
Section: Discussionmentioning
confidence: 99%
“…The choice of H. pylori eradication scheme conformed to the Fifth Chinese national consensus report . A cut‐off value for serum vitamin D level was set at 10 ng/mL because a study from Turkey has reported that 10 ng/mL may be the cut‐off value that affects H. pylori eradication . Finally, a 13 C‐UBT was repeated between 4 and 8 weeks after the treatment was completed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Repeated use of previously failed treatment combinations also contributes to poor eradication rates, highlighting the importance of efficient documentation of treatment histories. Treatment failure occurred more frequently in patients with 25‐OH vitamin D deficiency, whereas supplementing eradication therapy with vitamin C and E has no effect . A Japanese study found lower eradication rates with standard triple therapy in younger cohorts, perhaps reflecting poorer compliance …”
Section: Factors Of Treatment Failurementioning
confidence: 99%